Making your mind [videorecording (DVD)] : molecules, motion, and memory. - Kandel, Eric R.; Jassell, Thomas M. (Holiday lectures on science., 2009)
"Two leading neuroscientists [Eric R. Kandel, Thomas M. Jessell] discuss our current understanding of memory and brain development"--Container.